Student Management and Its Influence on Non-Academic Achievement at UPT SMP Negeri 1 Sungai Rumbai - Gustianti, Rima; Syoviana, Elvi; Andre, Lesis; Yunanda, B.R.E. (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The background of this research highlights that education should not only focus on academic achievement but also encompass the holistic development of students’ potential, including in non-academic areas. Non-academic achievements—such as in sports, arts, leadership, and other extracurricular activities—play a vital role in shaping students’ character, social skills, and self-confidence. Therefore, effective student management is essential to support and facilitate the development of these achievements.This research aims to describe and analyze the role of student management in fostering non-academic achievements at UPT SMPN 1 Sungai Rumbai. Non-academic achievements are key indicators in the comprehensive development of students’ character and potential, including in areas such as sports, arts, organizations, and other skills. This study employs a qualitative approach with a descriptive method. Data collection techniques include observation, interviews, and documentation. The research informants consist of the principal, vice principal of student affairs, extracurricular activity supervisors, and students actively involved in non-academic activities.The research findings show that student management at UPT SMPN 1 Sungai Rumbai has been implemented in a structured and systematic manner, from program planning and extracurricular implementation to activity evaluation. Full support from the school, supervisors, and active student participation are the main factors contributing to non-academic achievements. Additionally, the presence of a variety of extracurricular programs aligned with students’ interests helps foster improved performance. The conclusion of this study is that effective student management plays a crucial role in developing and enhancing students’ non-academic achievements.